On the genesis of the 2013 Bachat earthquake - G. G. Kocharyan; S. B. Kishkina; A. M. Budkov; G. N. Ivanchenko (Геодинамика и тектонофизика)
The ML 6.1earthquake that occurred on June 18, 2013 in Kuzbass is the strongest seismic event related to mining operations in this region. Opinions about its genesis differ. On the one hand, its hypocenter and most aftershocks occurred directly underneath the Bachat open-pit mine, which suggests that this seismic event was due to anthropogenic impacts. On the other hand, the earthquake focus was located at a depth of several kilometers, which, according to some authors, argues against the anthropogenic factor– the technogenic change in the parameters of the stress field was insignificant againstthe lithostatic pressure and, especially, the rock strength (e.g. [Lovchikov, 2016]).Our study aims to discover and assess an impact ofthe mining operations in the near-surface areas of the crust, investigate whether the Bachat earthquake was caused by the mining operations, and clarify which processes in particularwere the most probable triggers of dynamic movement in the Bachat earthquake source. The probable geometrical parameters of the fault plane were estimated from the structural and tectonic conditions of the study area and the published locations of the aftershocks [Emanov et al., 2017]. It is established that seimic events of magnitudes similar to that of the Bachat earthquake cannot be caused by the overall anthropogenic load on the area, and it is unlikely that such a strong earthquake may occur due to the direct effects of seismic vibrations resulting from mass explosions during the mining operations. Our analytical models and numerical simulations, as well as the analysis of seismological observation data show that the most probable factor that initiated dynamic movements in the earthquake source wasthe extraction of the huge rock volume and its transportation from theBachat open-pit mine. It should be noted that the size of the zone, wherein the geomechanical initiation criteria are met, is considerably larger than the critical size of a nucleation zone for a M 6 earthquake. However, open-pit mining operations can hardly affect the localization of strong earthquakesources. Mining operations can only trigger a seismic event that has been already prepared by the natural evolution of the crust.